Phytochemical Constituents, HPLC-PDA-ESI-MS/MS Profile and Bioactivities of Roots and Rhizomes of Prosopis farcta (Banks & Sol.) J. F. Macbr. - Ahmed, Eman F.; Sleem, Amany A.; Abbas, Fawkeya A.; El-Shafae, Azza M.; El-Domiaty, Maher M. (Natural Products Journal, The, 2020)
Background: The literature survey revealed that there are no sufficient phytochemical and biological studies on the roots and rhizomes of Prosopis farcta (Banks & Sol.) J. F. Macbr., therefore, the present work is concerned with the phytochemical and biological evaluation of this plant. Methods: The shade-dried roots and rhizomes were powdered together, extracted by 85% ethanol and subjected to phytochemical investigation. Biologically, the antioxidant, antidiabetic, cytotoxic, antiallergic and antimicrobial activities were evaluated. Results: The phytochemical investigation resulted in the isolation of 14 compounds including the fatty acid derivative, threo- methyl 9, 10-dihydroxyoctadecanoate (5), that is isolated for the first time from a natural source, in addition to the identification of 72 compounds by HPLC-PDA-ESIMS/ MS analysis including organic acids and their derivatives, flavonoids, anthraquinones and lignan derivatives. Biologically, threo- methyl 9, 10-dihydroxyoctadecanoate (5) exerted a potent cytotoxic effect against human lung carcinoma (A-549) and human colon carcinoma (HCT-116) cell lines. The total alcoholic extract showed a potent DPPH scavenging activity, a significant decrease in the blood glucose level in alloxan-induced diabetic rats and a mild antibacterial effect against Bacillus subtilis, Staphylococcus aureus (G +ve bacteria) and Escherichia coli (G –ve bacteria). Conclusion: This is the first report on the isolation and identification of threo- methyl 9, 10- dihydroxyoctadecanoate (5) from a natural source, and this novel compound exhibited potent cytotoxic activities against A-549 and HCT-116 cell lines. Moreover, this is the first HPLC-PDA-ESIMS/ MS profiling for this plant.
Keywords: cytotoxic